TiO2 photocatalytic degradation of cholesterol: SIMS study. (17th July 2012) - Prochazka, M.; Stupavska, M.; Jerigova, M.; Velic, D.
<x xml:space="preserve">Abstract</x> TiO2 is an efficient photocatalyst for chemical degradation. Nanocrystalline TiO2 is used in the form of film supported on glass substrate. Since the photocatalytic process is occurring on the surface, a surface‐sensitive technique as a direct probe is desirable. In order to study TiO2 photoactivity and photodegradation of cholesterol, as a model biomolecule, secondary ion mass spectrometry is utilized. Cholesterol (C27H46O), stated as M, with mass of 386.65 u, adsorbed on TiO2 surface, activated with water, and irradiated with different ultraviolet (UV) exposure times is characterized under impact of 25‐keV Bi+ primary ions. The molecular positive ions in the forms of M–OH and M–H with masses of 369.3 u and 385.3 u, respectively, are of main interest. Due to the specific group of OH, the M‐OH molecular ion might be considered as the primary identification species of the intact cholesterol molecule. The intensities of cholesterol fragment ions M–C5H10, M–C7H14, M–C7H14OH, M + C4H7, M + C4H9O, M + C4H9O2, M + C8H15, and 2 M–2(C8H17), 2 M–2(C7H15) decrease significantly after 7 h of UV exposure. Intensities of M–OH and M–H peaks decrease after 24 h by 88% and 62%, respectively. These measurements show the potential to degrade cholesterol, as a main bacteria membrane component and in such a way to terminate bacteria effectively. Copyright © 2012 John Wiley & Sons, Ltd.